ENNIS DEL MARR’S FLUID GENDER IN ANNIE PROULX’S BROKEBACK MOUNTAIN SHORT STORY - LUTVIANTO, GALIH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Brokeback  Mountain,  Judith  Butler’s  Queer  theory,  Homosexuality,Performativity, GenderJudith Butler proposed a new perspective in the queer theory which says that  sex isalready gendered, and from the statement itself it  can be said that  both of the category is actually a social constructed category.  From Butler’s theory also it can be said if someone gender is a fluid substance which can be understood that the identity proposed by Butler can suit in every place to adjust with the conditions. The researcher conduct a research on gender fluid in “Brokeback Mountain” short story where Ennis del Marr shows the gender fluid.The aims of this research are to analyze and explain the meaning of the message inside the short story. This research is analyzed by using the qualitative research design that the data are collected from the short story to be analyzed. The data are analyzed with Judith Butler’s queer theory. Since the problems that appears deal with the confusion and the trouble of the gender,  Judith  Butler’s  queer  theory  is  used  in  this  research.  Therefore,  from  Butler’s statement  it  helps to understand the character’s identity and inner  conflict  which shifting since it is violate the values in the society.The result of the study shows that gender as an unstable identity appears as the effect of the social construction. Someone’s identity also recognized with following some steps that will  help the identity to be understood.  The  steps  which appear  are:  gender  is  unstable identity, gender is performative, and there is no identity behind the expression of the gender. The gender identity also appears as the effect of the social judgment that will reconstruct the gender itself.